Tyrosine‐Based Ionic Liquid Crystals: Switching from a Smectic A to a Columnar Mesophase by Exchange of the Spherical Counterion. Issue 46 (13th October 2016) - Neidhardt, Manuel M.; Wolfrum, Manpreet; Beardsworth, Stuart; Wöhrle, Tobias; Frey, Wolfgang; Baro, Angelika; Stubenrauch, Cosima; Giesselmann, Frank; Laschat, Sabine
Abstract: Synthetic strategies were developed to preparel ‐tyrosine‐based ionic liquid crystals with structural variations at the carboxylic and phenolic OH groups as well as the amino functionality. Salt metathesis additionally led to counterion variation. The liquid‐crystalline properties were investigated by differential scanning calorimetry (DSC), polarizing optical microscopy (POM) and X‐ray diffraction (WAXS, SAXS). The symmetrical ILC chlorides bearing the same alkyl chain at both the ester and ether but either an acyclic or cyclic guanidinium group displayed enantiotropic SmA2 mesophases with phase widths of 31–88 K irrespective of the head group. It was particularly the replacement of chloride in the acyclic guanidinium ILC by hexafluorophosphate that induced a phase change from SmA2 to Colr . This phase change was attributed to a higher curvature of the interface due to the larger anion, which increased the effective head group cross‐sectional area of the amphiphilic ILC. The unsymmetrical acyclic guanidinium chlorides, bearing a constant C14 ester and variable alkyl chains on the phenolic position, formed enantiotropic SmA2 phases. The derivative with the largest difference in chain lengths, however, displayed a Colr phase, resulting from discoid aggregates of the cone‐shaped guanidinium chloride. The results are discussed in terms of the packing parameters, which indicate that the phase behaviour of the thermotropic tyrosine‐based ILCs shows analogies to those of lyotropic liquid crystals. Abstract : The role of the anion : Hexafluorophosphate induces a mesophase change from SmA to Colr for novell ‐tyrosine‐based guanidinium ionic liquid crystals. Due to the large PF6 anionic radius, the formation of discoid aggregates of ten self‐assembled molecules is preferred, leading to a columnar packing. This argument is further rationalized by considering a strongly increased interfacial curvature in analogy to the packing model of lyotropic liquid crystals.